Development of Avinit duplex technology to increase the wear resistance of the gearbox separator - Sagalovych, Alex; Popov, Viktor; Sagalovych, Vladislav; Dudnik, Stas; Edinovych, Andrey; Stupakov, Alexander (Mechanics and Advanced Technologies, 2020)
The Avinit duplex technology has been developed by means of plasma precision nitriding of Avinit N and the subsequent application of a multifunctional antifriction coating Avinit C on the surfaces of rubbing bodies and perceives power loads. The influence of the duplex process on the dimensions of the parts was investigated; the properties of the nitrided layer and the parameters of Avinit coatings were studied. Avinit duplex technology ensures the application of highly adherent, high-quality multifunctional anti-friction wear-resistant Avinit C coatings on complex-profile parts. Using the developed Avinit duplex technology, a pilot batch of separators for the freewheel of the main gearbox of the helicopter was manufactured. All parameters of the separator, manufactured using the Avinit duplex technology, fully comply with the technical, metallurgical and metallographic requirements of design documentation (thickness and microstructure of the nitrided layer, no brittleness, thickness and hardness of the coating, preservation of geometric parameters with an accuracy of 0.5 microns). The Avinit coated freewheel separator has been successfully tested as part of the main gearbox for a helicopter at a full-scale stand. As shown by the test results, the use of the developed Avinit duplex technology ensures the complete absence of fretting wear of the working surfaces, which is common for serial separators.